Looking For Diamond From Fatherless Family: Descriptive Study of Entrepreneurial Characteristics on Fatherless Teen - Yuliawati, Livia (ANIMA Indonesian Psychological Journal, 2010)
Some entrepreneurs came from fatherless family, for example Frederick W Smith as the founder of FedEx, Jerry Yang as Yahoo!-Creator, Stephen Tong as Reformed Evangelical Movement Founder, and also Ciputra as the Ciputra Group owner. They experienced many difficult conditions and those experiences formed their character to be entrepreneurs as they are today. The purpose of this study was to find characteristics of fatherless teen successful entrepreneurs. Subjects in this research were 13-18 years old-junior and senior high school students from fatherless family (N=85). Data were collected through questionnaire consisting statement about entrepreneurial characteristics and questions related to their fatherless family. The result and discussion will be explained in this article. Beberapa entrepreneur lahir dari keluarga tanpa ayah, seperti Frederick W Smith sebagai pendiri FedEx, Jerry Yang sebagai pencipta Yahoo!, Stephen Tong sebagai pendriri Gerakan Reformed Injili, dan juga Ciputra sebagai pemilik Grup Ciputra. Mereka bercerita bahwa mereka telah mengalami banyak situasi sulit dan pengalaman ini mengasah karakter mereka menjadi entrepreneur seperti sekarang. Fenomena tersebut mendorong penelitian ini yang bertujuan untuk menemukan karakteristik entrepreneur pada remaja tanpa ayah. Subjek penelitian ini adalah siswa SMP dan SMA dari keluarga tanpa ayah (N=85). Data dikumpulkan melalui kuesioner yang berisi pernyataan tentang karakteristik entrepreneurship dan pertanyaan terkait keluarga tanpa ayah. Hasil dan diskusi akan dijelaskan dalam artikel ini.